Surgical Outcome of Patients with Hyperparathyroidism in a Nonspecialist Surgical Ward - Roslani, April Camilla; Chang, N.L.W. (Malaysian Medical Association, 2006)
Aim of the study was to audit patients who had undergone parathyroidectomy in the University of Malaya Medical Centre (UMMC) and compare surgical outcomes with that in the literature. Data on demography, aetiology, surgical indications, pre-operative localization, surgery and complications was obtained retrospectively from medical records of patients undergoing parathyroidectomy between 1st October 2000 to 31st October 2005. Twelve patients were identified. Mean age was 50.6 years. 67% were females. The ratio of Chinese, Malays and Indians was 7:4:1. Most surgeries were performed in the last two years (91.7%). Aetiology was mainly tertiary hyperparathyroidism (83%). All patients had pre-operative ultrasound localization. Half underwent total parathyroidectomy without autotransplantation. There were no re-do operations. Mean duration of surgery was 1.96 hours. All patients had abnormal calcium levels at some point following surgery, but 90% were normocalcaemic at last follow-up. Other complications were recur ent laryngeal nerve injury (one) and wound infection (one). There were no peri-operative mortalities. The mean duration of hospital stay was 7.75 days (range 3-17 days). The median duration of follow up was 11 months. The outcome of parathyroidectomy in UMMC is satisfactory with few major complications. Despite this, intensive effort is needed to further improve these results to match those obtained in specialist endocrine centres.